A mixed methods study of the administration of flucloxacillin oral liquid; identifying strategies to overcome administration issues of medicines with poor palatability. (16th September 2016) - Rouse, Claudia; Mistry, Punam; Rayner, Oli; Nickless, Jess; Wan, Mandy; Southern, Kevin W.; Batchelor, Hannah K.
Abstract: Background: The palatability of flucloxacillin oral liquid is poor. Parents/carers use strategies to aid the administration of poorly palatable medicines. Aim: To assess views on the palatability of flucloxacillin oral liquid and identify factors associated with successful administration. Methods: A mixed methods study which included a structured review of online forums and a survey of parent/carers of children with cystic fibrosis (CF) to obtain parent/carer views on the administration of flucloxacillin oral liquid. Results: A total of 18 strategies to aid the administration of flucloxacillin suspension to children were identified on 10 different public online forums. A total of 255 responses to the open online survey were received with 47% of respondents reporting that administration of flucloxacillin was more problematic compared to other medicines and 38% reporting the need to improve the palatability. The brand of flucloxacillin oral liquid significantly influenced the degree of difficulty associated with administration to children. A significant relationship was found between the concentration of flucloxacillin and the reported number of doses successfully administered. The use of food and drink to aid administration was more commonly stated in online forums (44%) compared to the survey data of parents/carers of children with CF (15.9%). Conclusion: The administration of flucloxacillin oral liquid is perceived as a challenge by parent/carers because of palatability. For chronic use, a more concentrated oral liquid and certain brands are likely to improve acceptability.